Molekulární fylogenetika primárních endosymbiontů hmyzu - Skála, Benjamín (Jihočeská univerzita, 2009)
Molecular phylogeny and evolution of the bacterial Primary symbionts in insects pose several complex questions in respect to the methodology and theory of molecular phylogenetics. This thesis provides an introduction to the biology of the Primary symbionts and the main aspects of their phylogeny.
Molecular Phylogenetics of Primary Endosymbiots of Insects